Performance of 113Sn/113mIn Generator Prototype based on Zirconium Oxide for Radiotracer Applications in Industry - Duyeh Setiawan; Ade Suherman; Titin Sri Mulyati (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2021)
This paper describes the results of the research of 113Sn/113m radioisotope generator at the Centre for Applied Nuclear Science and Technology - National Nuclear Energy Agency with the aim of making radioisotope generator for radiotracer applications in industry. This research discussed the need of short half-life radiotracer for several material phases such as oil, water, gas and solid. Based on desired physical properties of half life, radiation type and energy, 113mIn radioisotope was selected. Thus, the performance of 113Sn/113mIn generator prototype based on zirconium oxide was determined for this purpose. The final product specification in the form of 113mInCl3 is clear solution, pH 2 with obtained yield of 95 %, radionuclide purity of 95 % and radiochemical purity of 95 %.